Meninjau Kembali Nasab dan Kewarisan dalam Hukum Islam: Pengakuan Hukum dan Status Anak yang Lahir di Luar Perkawinan di Indonesia - Ahmad Sukris Sarmadi; Anwar Hafidzi; Latifah Abd Majid (Syariah: Jurnal Hukum dan Pemikiran, 2025)
This study examines the legal status and protection of children born out of wedlock within the Indonesian legal system, highlighting the tension between religious norms and human rights principles. The primary objective is to analyze the legal dimensions of lineage (nasab), inheritance rights, and civil recognition of such children based on Islamic law, national legislation, and Constitutional Court jurisprudence. Employing a normative legal method and qualitative analysis of statutory regulations, religious doctrines, and court decisions, the study finds that Islamic law recognizes only maternal lineage for out-of-wedlock children, excluding them from paternal inheritance. However, Constitutional Court Decision No. 46/PUU-VIII/2010 affirms civil recognition through biological evidence, though its implementation faces administrative and societal resistance. The findings imply the urgent need for inclusive legal reform, harmonization between Islamic and national law, and strengthened child protection mechanisms in practice.